Temperature and Humidity Monitoring in Hydroponic Cultivation Based on Internet of Things: Dataset Development for Smart Agriculture - Barus, Simon Prananta; Seo, Jeriko Ichtus (ISB Atma Luhur, 2025)
This research is a continuation of the previous research, entitled